Pelaksanaan BPJS Ketenagakerjaan Sebagai Perlindungan Hukum Terhadap Tenaga Kerja - Sitanggang, Ariani; Shelomita, Ruth; Lituhayu, Jovita; Widya, Diny (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study examines the role of the government and BPJS Ketenagakerjaan in improving the quality and effectiveness of legal protection for workers in Indonesia. This article analyzes the policies that have been implemented, the programs that have been implemented, and the challenges faced in efforts to protect workers' rights. The results of the study indicate that both the government and BPJS Ketenagakerjaan have a very strategic role in creating a safe and fair work environment. However, stronger synergy is needed between the two to overcome various obstacles that still exist, such as low public awareness and the complexity of claim procedures. This article provides policy recommendations to improve the effectiveness of legal protection for workers.